Augmented Reality Berbasis Android Sebagai Media Pembelajaran Sistem Tata Surya - Yulia Fatma; Armen Salim; Regiolina Hayami (Universitas Muhammadiyah Riau, 2021)
Along with the development, the application can be used as a medium for learning. Augmented Reality is a technology that combines two-dimensional’s virtual objects and three-dimensional’s virtual objects into a real three-dimensional’s then projecting the virtual objects in real time and simultaneously. The introduction of Solar System’s material, students are invited to get to know the planets which are directly encourage students to imagine circumtances in the Solar System. Explenational of planets form and how the planets make the revolution and rotation in books are considered less material’s explanation because its only display objects in 2D. In addition, students can not practice directly in preparing the layout of the planets in the Solar System. By applying Augmented Reality Technology, information’s learning delivery can be clarified, because in these applications are combined the real world and the virtual world. Not only display the material, the application also display images of planets in 3D animation’s objects with audio.